Implementasi Politik Dan Etika Pendidikan Dalam Mewujudkan Kesetaraan Gender Di Lingkungan Pendidikan - Deni Setyawan; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Gender equality in education is an important aspect in creating a fair, inclusive, and humane educational system. This study aims to determine the implementation of educational politics and ethics in realizing gender equality at SMP Negeri 2 Plumpang. This research uses a qualitative research method with a descriptive approach. Data collection techniques were carried out through interviews with one of the teachers, Mrs. Ike, as the main informant. The results of the study indicate that the school has implemented the principles of gender equality through non-discriminatory policies, providing equal opportunities for students in both academic and non-academic activities, and applying educational ethics that emphasize justice and respect for every individual regardless of gender. In addition, the supporting factors for the implementation of gender equality include school policies, teachers’ awareness, support from the principal, an inclusive curriculum, and parental participation. However, there are still obstacles in the form of cultural stereotypes and public understanding that still differentiate the roles of men and women. Therefore, the implementation of educational politics and ethics has an important role in creating a school environment that is inclusive, safe, and supportive of the optimal development of students’ potential.